THE EFFECTIVENESS OF ONLINE LEARNING TO STUDENT LEARNING ACTITIVITIES OF FKIP UNIVERSITAS VETERAN BANGUN NUSANTARA SUKOHARJO (CASE STUDY: COVIF-19 EMERGENCY DISASTER 21 MARCH-31 MAY 2020) - Ayuni Margiyanti; Pranichayudha Rohsulina; Muh. Husyain Rifai (Journal of Geography Science and Education, 2020)
This study aimed to discover: (1) The effectiveness of online learning to student learning activities of the Faculty of Teacher Training and Education in Universitas Veteran Bangun Nusantara Sukoharjo during the COVID-19 disaster response period of 2020. (2) The readiness form of FKIP & The Univet Institution in online learning utilization during the COVID-19 disaster response period of 2020. The method in the study was qualitative descriptive and the sampling technique used was Proportionate Stratified Random Sampling. The data collection technique used was using observations, questionnaires, and documentation. The data analysis technique used was qualitative data analysis. Based on the study, it can be concluded that: (1) The online learning utilization to student learning activities in the Faculty of Teacher Training and Education has been effective, but it still needs improvement or refinement in several aspects. (2) The Faculty of Teacher Training and Education's lecturers using online learning during the COVID-19 disaster response period were mostly ready, but need gradual training to be professional lecturers. (3) The presence of multimedia components and sufficient e-learning procurement by the institution of Universitas Veteran Bangun Nusantara Sukoharjo for online learning during the COVID-19 disaster response period.